Factors Influencing Occupational Diversification among Farmers in Khordha District of Odisha - Jayasingh, Debi Kalyan; Mishra, Bishnupriya (Indian Journal of Extension Education, 2024)
Farmers of the Khordha district of Odisha have been proactively involved in diversifying their occupations from conventional on-farm like crops to off-farm sectors like storage, post-harvest, input dealers, etc and even in non-farm like government jobs, restaurants, renting, etc. A study was conducted to assess factors’ influence on farmers’ occupational diversification during 2022-23. Data collection was conducted by personal interview method. 240 farmers were picked up as respondents under simple random sampling. The majority of the farmers expressed to the medium extent of occupational diversification. Factors such as education, the number of non-farm activities, achievement motivation, and management orientation were found to show significant contributions towards occupational diversification as these along with others managed to elucidate about sixty-four percent of variation on diversification.
Keywords: Relationship; Chi-square test; Regression; Occupational diversification; Farmers; Odisha